2011
DOI: 10.1086/660102
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Vignettes Provide an Understanding of Antibiotic Prescribing Practices in Neonatal Intensive Care Units

Abstract: Objective To use clinical vignettes to understand antimicrobial prescribing practices in neonatal intensive care units (NICUs). Design Vignette-based survey. Setting Four tertiary care NICUs. Participants Antibiotic prescribers in NICUs. Methods Clinicians from 4 tertiary care NICUs completed an anonymous survey containing 12 vignettes that described empiric, targeted, or prophylactic antibiotic use. Responses were compared with Centers for Disease Control and Prevention guidelines for appropriate use.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 15 publications
(21 reference statements)
2
16
0
Order By: Relevance
“…In a multi-center survey of neonatal clinicians, 37% (52/137) of respondents indicated that they would use meropenem and metronidazole for suspected NEC. 25 In contrast, to increase the likelihood of adequate initial therapy, a beta-lactam agent paired with an aminoglycoside agent (e.g., piperacillin/tazobactam plus tobramycin) may have role in empiric therapy for critically ill patients at risk of infection with multidrug- resistant pathogens. Once susceptibility results are known, use of a single beta-lactam agent is preferred, since, in adults, combination therapy has not shown to reduce mortality, morbidity, or protect against the development of resistance for gram-negative pathogens.…”
Section: Starting Antibiotics--selecting Empiric Therapymentioning
confidence: 99%
“…In a multi-center survey of neonatal clinicians, 37% (52/137) of respondents indicated that they would use meropenem and metronidazole for suspected NEC. 25 In contrast, to increase the likelihood of adequate initial therapy, a beta-lactam agent paired with an aminoglycoside agent (e.g., piperacillin/tazobactam plus tobramycin) may have role in empiric therapy for critically ill patients at risk of infection with multidrug- resistant pathogens. Once susceptibility results are known, use of a single beta-lactam agent is preferred, since, in adults, combination therapy has not shown to reduce mortality, morbidity, or protect against the development of resistance for gram-negative pathogens.…”
Section: Starting Antibiotics--selecting Empiric Therapymentioning
confidence: 99%
“…A previous study suggested that clinical vignettes may be a useful way to assess physicians' practices in an outpatient setting [14]. The clinical relevance of this method in a wide panel of clinical situations such as trauma triage, antibiotic prescriptions in neonatal ICUs, crisis-oriented anaesthesia events, regional anaesthesia or ethical considerations has been recently suggested [15][16][17][18][19]. This modern method seems suited for evaluating the knowledge of a group and subsequently well adapted to the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Case vignettes of MDR-GNB infections could be used to supplement the lack of knowledge and familiarity experienced by some providers. 28 To be effective, the educational strategy should address general principles such as mechanisms of resistance expressed by MDR-GNB, pharmacokinetic principles for different types of infections, and methods of susceptibility testing. Content should also include locally relevant information such as the institutional antibiogram, pathogen distribution, relevant empiric therapy and targeted therapy, and interpretation of relevant microbiology reports.…”
Section: Discussionmentioning
confidence: 99%